BASIC ELECTRICAL AND INSTRUMENTATION ENGINEERING - Sivaraman, P. , author; Sharmeela, C., author; Nayagi, A. Thaiyal , author; Mahendran, R., author (Hoboken, NJ : John Wiley & Sons, Inc., 2021)
Includes bibliographical and references